2003
DOI: 10.1021/ic034737b
|View full text |Cite
|
Sign up to set email alerts
|

Dirhodium Formamidinate Compounds with Bidentate Nitrogen Chelating Ligands

Abstract: The reactions of [Rh(2)(DTolF)(2)(CH(3)CN)(6)][BF(4)](2) (1) (DTolF = N,N'-di-p-tolylformamidinate) with 2,2'-bipyridine (bpy) and 1,10-phenanthroline (phen) proceed with substitution of CH(3)CN molecules to give products with the N-N ligands chelating in an equatorial-equatorial (eq-eq) fashion. Compound 1 reacts with 1 equiv of bpy to yield a mixture of [Rh(2)(DTolF)(2)(bpy)(CH(3)CN)(3)][BF(4)](2).(CH(3))(2)CO (2a) and [Rh(2)(DTolF)(2)(bpy)(CH(3)CN)(4)][BF(4)](2) (2b). Compound 2a crystallizes in the monocli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…In particular, the single‐crystal X‐ray crystallographic determination of HH cis ‐[Rh 2 (DTolF) 2 (9‐EtGuaH) 2 (NCCH 3 )](BF 4 ) 2 revealed bridging 9‐EtGuaH groups binding to equatorial sites of the dirhodium unit through N7/O6. 23 Related studies involving the reactions of cis ‐[Rh 2 (DTolF) 2 (CH 3 CN) 6 ](BF 4 ) 2 with NN chelates, which mimic the binding of two adjacent DNA bases (2,2′‐bipyridine and 1,10‐phenanthroline), demonstrated that the latter bind to the dirhodium core in a chelating fashion by substituting acetonitrile molecules in equatorial positions 24…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the single‐crystal X‐ray crystallographic determination of HH cis ‐[Rh 2 (DTolF) 2 (9‐EtGuaH) 2 (NCCH 3 )](BF 4 ) 2 revealed bridging 9‐EtGuaH groups binding to equatorial sites of the dirhodium unit through N7/O6. 23 Related studies involving the reactions of cis ‐[Rh 2 (DTolF) 2 (CH 3 CN) 6 ](BF 4 ) 2 with NN chelates, which mimic the binding of two adjacent DNA bases (2,2′‐bipyridine and 1,10‐phenanthroline), demonstrated that the latter bind to the dirhodium core in a chelating fashion by substituting acetonitrile molecules in equatorial positions 24…”
Section: Introductionmentioning
confidence: 99%
“…The diimine-coordinated, formamidinate-bridged Rh 2 II,II dimers were synthesized via a stepwise approach to permit purification at each step. [7,19,23,34,35] As depicted in Figure 1, the final step involves refluxing 1 with two equivalents of the bridging np or bidentate chelating dap diimine ligand in CH 3 CN to afford 3 as a dark purple powder (69%) or 4 as a dark 8 maroon powder (75%), respectively. The formation of the diimine-bridged dimer was complete within 3 hr, indicating the rapid nature of the coordination of the np ligand to the dirhodium core.…”
mentioning
confidence: 99%
“…The bond distances found trans to guanidinate nitrogen atoms are slightly longer than those cis to them. This lengthening trend of trans groups is similar to the trans influence of both guanidinate and formamidinate groups relative to carboxylates. ,, Meanwhile, the average N–C bond lengths were 1.357 Å for – hpp and 1.331 Å for – DAniF, which are consistent with the delocalized charge in these bonds.…”
Section: Resultsmentioning
confidence: 99%